Advances in electron beam technology for environmental and biotechnological applications at Fraunhofer FEP. Issue 1 (1st February 2023) - Teichmann, T; Dincklage, L; Schaap, L L; Schreuder, D; Blüthner, R; Winckler, F; Schopf, S; König, U; Zimmermann, B; Mattausch, G
Abstract: An expanding part of electron beam technology developed at Fraunhofer FEP tackles ecological and biotechnological challenges of highest relevance. Antimicrobial and fungicidal effects of electron beam are exploited in the chemical-free phytosanitary treatment of seeds. Chemical pollutants but also pathogens in gaseous effluents and waste water can be efficiently neutralized. Medical products such as tools, packaging and implants can be sterilized, disinfected, or even biologically advantageously functionalized. Viruses can be inactivated via electron beam to produce vaccines with an excellent antigen conservation leading to a high degree of immunization with good reproducibility, but without the usage of additional chemicals. Plasma synthesis in electron beam-sustained discharges allows for an exceptionally efficient energy transfer to non-reactive greenhouse gases like CO2 and CH4 and is a promising approach to the economical, scalable production of media for sustainable chemical energy storage (Power to X - PtX), driving the energy transition and reducing greenhouse gases. The publication gives an overview of the recent advances of electron beam technology at Fraunhofer FEP in these emerging fields of application.